(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper we investigate the existence and uniqueness of common ï¬xed point theorems for certain contractive type of mappings. As an application the existence and uniqueness of common solutions for a system of functional equations arising in dynamic programming are discuss by using the our results.